Effects of Hydrostatic Pressure on Electrical Retinal Activity in a Multielectrode Array-Based ex vivo Glaucoma Acute Model - Ingensiep, Claudia; Schaffrath, Kim; Walter, Peter; Johnen, Sandra (Frontiers in Neuroscience, 2022)
Glaucoma is a heterogeneous eye disease causing atrophy of the optic nerve head (ONH). The optic nerve is formed by the axons of the retinal ganglion cells (RGCs) that transmit visual input to the brain. The progressive RGC loss during glaucoma leads to irreversible vision loss. An elevated intraocular pressure (IOP) is described as main risk factor in glaucoma. In this study, a multielectrode array (MEA)-based ex vivo glaucoma acute model was established and the effects of hydrostatic pressure (10, 30, 60, and 90 mmHg) on the functionality and survival of adult male and female wild-type mouse (C57BL/6) retinae was investigated. Spontaneous activity, response rate to electrical and light stimulation, and bursting behavior of RGCs was analyzed prior, during, and after pressure stress. No pressure related effects on spontaneous firing and on the response rate of the RGCs were observed. Even a high pressure level (90 mmHg for 2 h) did not disturb the RGC functionality. However, the cells’ bursting behavior significantly changed under 90 mmHg. The number of spikes in bursts doubled during pressure application and stayed on a high level after pressure stress. Addition of the amino sulfonic acid taurine (1 mM) showed a counteracting effect. OFF ganglion cells did not reveal an increase in bursts under pressure stress. Live/dead staining after pressure application showed no significant changes in RGC survival. The findings of our ex vivo model suggest that RGCs are tolerant towards high, short-time pressure stress.